2006
DOI: 10.1038/sj.mp.4001894
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal hyperactivation during working memory task in untreated individuals with major depressive disorder

Abstract: The prefrontal cortex, a part of the limbic-thalamic-cortical network, participates in regulation of mood, cognition and behavior and has been implicated in the pathophysiology of major depressive disorder (MDD). Many neuropsychological studies demonstrate impairment of working memory in patients with MDD. However, there are few functional neuroimaging studies of MDD patients during working memory processing, and most of the available ones included medicated patients or patients with both MDD and bipolar disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
150
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(180 citation statements)
references
References 76 publications
(106 reference statements)
22
150
4
4
Order By: Relevance
“…Decreased activation was observed in response to targets overall collapsing the target subtypes in bilateral MFG, indicating the task importance in influencing fMRI results in MDD. Two recent studies in medication-free MDD patients revealed increased prefrontal activation during effortful cognitive tasks compared to the controls (Matsuo et al, 2006, Wagner et al, 2006. Although antidepressant medication use may influence the fMRI findings in MDD (Mayberg et al, 2000, Davidson et al, 2003, Fu et al, 2004, task differences may also greatly contribute to the discrepancy in findings across studies as evident by our current study (discrepancy of activation in the MFG to overall targets and target subtypes).…”
Section: Discussioncontrasting
confidence: 43%
“…Decreased activation was observed in response to targets overall collapsing the target subtypes in bilateral MFG, indicating the task importance in influencing fMRI results in MDD. Two recent studies in medication-free MDD patients revealed increased prefrontal activation during effortful cognitive tasks compared to the controls (Matsuo et al, 2006, Wagner et al, 2006. Although antidepressant medication use may influence the fMRI findings in MDD (Mayberg et al, 2000, Davidson et al, 2003, Fu et al, 2004, task differences may also greatly contribute to the discrepancy in findings across studies as evident by our current study (discrepancy of activation in the MFG to overall targets and target subtypes).…”
Section: Discussioncontrasting
confidence: 43%
“…One such disorder, clinical depression, has indeed been associated with increased task-evoked LPFC activity (45,46). Outside the context of psychopathology, however, the motive to minimize internal decision costs might serve a beneficial purpose, guiding behavior toward maximally efficient tasks and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CVLT is associated with hippocampal volume (Banos et al, 2004;Tischler et al, 2006) and frontal function (Baldo et al, 2002), the relationship between ACC function and memory processing measured by CLVT is unclear. Therefore, other neurocognitive tasks that activate ACC function (Gehring and Willoughby, 2002;Matsuo et al, 2007) are warranted to determine whether the BDNFVal66Met polymorphism participates in working memory processing related to ACC function in BD patients.…”
Section: Discussionmentioning
confidence: 99%